Paryż w literaturze polskiego oświecenia (kilka uwag) - Ryba, Janusz (Postscriptum Polonistyczne, 2020)
In literature, during the Polish Age of Enlightenment, the word Paris was above all a ‘label’, that symbolised an incredible town that provoked representatives of the Polish establishment to behave foolishly. The capital of France was rarely depicted in a realistic manner by visitors from Poland. Absurd and reprehensible attitudes, inspired by Paris, and described by eighteenth century writers, were numerous. For example, visiting Paris resulted in displays of unusual pride, and those who visited Paris regarded themselves as better and far above those who were not lucky enough to see the capital of France. The Polish elite followed Parisian fashion and adored objects produced there. The capital of France became the most desirable place to visit but Paris was the ruin of many Polish tourists. In Polish literature, between 1764 and 1795, the word Paris was only replaced once by a realistic image of the capital of France: in Krasicki’s novel Mikołaja Doświadczyńskiego przypadki. (1776).